The university reform from the State and the Nicolaita student radicalism, 1926-1935 (2018)
The article refers to a process of university reform that took place in the 1920s and 1930s in Michoacán. We specially focus on the rectorates of Jesús Díaz Barriga and Enrique Arreguín Vélez, two of the most important socialist leaders of that time. Other characters such as Natalio Vázquez Pallares, who, as well as Arreguín, ascended quickly from the student leadership to the university leadership. A common characteristic among these university students was their closeness to General Lázaro Cárdenas, Governor of Michoacán and President of the Republic in those years. One of the purposes of this paper is to show the participation of student organizations in a process of the university reform that proposed the establishment of a State University. For this purpose, student groups and university authorities joined forces with the support of the state and federal governments. The former played an important role as instruments of ideological propaganda and social control. The degree of political and ideological radicalization of the socialist student organizations helped to accelerate and deepen the implementation of the official educational policy in Michoacán and other places in the country. Groups such as the Nicolaita Student Council and the young revolutionaries block of Michoacan systematically fought against the political and ideological opponents of Cardenismo, which gave them a privileged place within the university structure.